Methods and applications of on-chip beam splitting: A review - Xu, Yuting; Tian, Zhongxing; Meng, Xiaoqin; Chai, Zhen (Frontiers in Physics, 2022)
The construction of large-scale integrated photonic circuit cannot be separated from the important role played by silicon-based optoelectronic devices. As a basic and important link in on-chip photon propagation, beam splitting is of great significance for the efficient utilization of sources and the compact integration of optoelectronic devices. It is widely used in power splitting, polarization separation, wavelength division multiplexing and other scenarios. This paper reviews the on-chip beam splitting methods in recent years, which are mainly divided into the following categories: y-branch, multimode interference coupling, directional coupling, and inverse design. This paper introduces their research status, including optimization design methods, functions and applications in large-scale quantum chips and optoelectronic hybrid integration, looking forward to providing a reference for the further research of beam splitting methods and the wide application of beam splitters in the frontier field in the future.